2011
DOI: 10.28945/1521
|View full text |Cite
|
Sign up to set email alerts
|

If We Build It, Will They Come? Adoption of Online Video-Based Distance Learning

Abstract: Technologies that enable interactive video lectures are becoming ubiquitous and affordable. The learning experience that video lectures offer students resembles in-class learning more than other options of distance learning. This study examines the adoption of interactive online video-based distance learning in a blended learning environment, where the students choose their mode of learning. It analyzes the enrollment of interactive online video classes in two introductory courses at the Open University of Isr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With the development of the information technologies and the elimination of the barriers to video production, using multimedia in education has increased. Especially through video lectures, students are offered a rich learning experience, because video lectures have the potential to increase student retention and achievement in distance and blended learning environments (Geri, 2011). Besides, they might help the students who are not able to attend the courses regularly (Wieling & Hofman, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…With the development of the information technologies and the elimination of the barriers to video production, using multimedia in education has increased. Especially through video lectures, students are offered a rich learning experience, because video lectures have the potential to increase student retention and achievement in distance and blended learning environments (Geri, 2011). Besides, they might help the students who are not able to attend the courses regularly (Wieling & Hofman, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Online video lectures have been successfully used for supporting face-to-face learning (Boton & Gregory, 2015;Brecht, 2012;Kinash, Knight, & McLean, 2015;Whatley & Ahmad, 2007;Wieling & Hofman, 2010), as well as in-class learning, e.g., when there is a need to show students visual elements (Ostashewski, Reid, & Ostashewski, 2016). However, online video lectures are not a silver bullet solution for solving the challenges of online learning (Geri, 2011;Guri-Rosenblit, 2009;Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Guri-Rosenblit in his higher education policy suggested that as people need socializing, students prefer face to face classes over online classes even if rich e-learning environment was provided 12 . Additionally, the students get easily distracted while attending classes from home by family members and or phone calls, which implies the importance of traditional classes over online classes 13 .…”
Section: Discussionmentioning
confidence: 99%